2022
DOI: 10.32598/cjns.4.31.338.1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rate of Acute Stroke in Iran: A Systematic Review and Meta-Analysis

Abstract: Background: There is limited data about the short-term stroke mortality rates for patients in treatment settings. Objectives: This study aimed to estimate the short-term stroke (in hospital, one month, one year) mortality rates in Iran through a systematic review and meta-analysis. Materials & Methods: We searched electronic databases, including three national (IranDoc, Megiran, SID) and four international (Scopus, PubMed, Web of Science, Google Scholar), from January 1990 to March 2020. We considered all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Increasing evidence has elucidated that increasing age is a crucial risk factor for stroke mortality, especially for the older population, who are more susceptible to physical and emotional challenges. [37] These challenges can trigger heightened perceived stress levels, exacerbating their coping mechanisms following the stroke. [11] In the current study, older poststroke survivors experiencing high levels of perceived stress tended to confront the stroke in a maladaptive manner, showing resistance to accepting their altered reality and exhibiting negative emotional responses like anxiety, fear, and depression.…”
Section: The Relationship Between Perceived Stress and Ptgmentioning
confidence: 99%
“…Increasing evidence has elucidated that increasing age is a crucial risk factor for stroke mortality, especially for the older population, who are more susceptible to physical and emotional challenges. [37] These challenges can trigger heightened perceived stress levels, exacerbating their coping mechanisms following the stroke. [11] In the current study, older poststroke survivors experiencing high levels of perceived stress tended to confront the stroke in a maladaptive manner, showing resistance to accepting their altered reality and exhibiting negative emotional responses like anxiety, fear, and depression.…”
Section: The Relationship Between Perceived Stress and Ptgmentioning
confidence: 99%
“…In Nikbakht et al's meta-analysis study of 17 articles, the hospital mortality rate was 18.71%, and the one-month mortality rate was 23.43% (12). Also, in the study of Krishnamurthi et al, the global prevalence of hemorrhagic stroke was reported as 3,725,085, and the prevalence of ischemic stroke was 7,258,216 (13).…”
Section: Introductionmentioning
confidence: 99%
“…The most common type of stroke is ischemic stroke, which arises after embolism, thrombolysis, or cryptogenic mechanisms in which blood flow to the brain is damaged. 1 Early prediction of the outcome in patients with ischemic stroke is significant. Reliable prognostic markers existing during the initial phase after acute stroke could help clinical decisionmaking.…”
mentioning
confidence: 99%